Catalytic Enantioselective Intermolecular Benzylic C(sp3)−H Amination. Issue 24 (8th May 2019) - Nasrallah, Ali; Boquet, Vincent; Hecker, Alexandra; Retailleau, Pascal; Darses, Benjamin; Dauban, Philippe
Abstract: A practical general method for asymmetric intermolecular benzylic C(sp 3 )−H amination has been developed by combining the pentafluorobenzyl sulfamate PfbsNH2 with the chiral rhodium(II) catalyst Rh2 (S‐tfptad)4 . Various substrates can be used as limiting components and converted to benzylic amines with excellent yields and high levels of enantioselectivity. Additional key features for the reaction are the low catalyst loading and the ability to remove the Pfbs group under mild conditions to give NH‐free benzylic amines. Abstract : Benz to benz : A practical method for asymmetric intermolecular benzylic C(sp 3 )−H amination is reported. The latter is based on the combination of the pentafluorobenzyl sulfamate PfbsNH2 with the chiral rhodium(II) catalyst Rh2 ( S ‐tfptad)4 . Various substrates are converted to benzylic amines with excellent yields and high levels of enantioselectivity. The Pfbs group can be removed under mild conditions to afford the free‐NH benzylic amines.